Enantioselective Dechlorination of Polychlorinated Biphenyls in Dehalococcoides mccartyi CG1 - Yu, Ling (Appl Environ Microbiol, 2018)
Reductive dehalogenation mediated by organohalide-respiring bacteria plays a critical role in the global cycling of organohalides. Nonetheless, information on the dehalogenation enantioselectivity of organohalide-respiring bacteria remains limited. In this study, we report the enantioselective dechlorination of chiral polychlorinated biphenyls (PCBs) by Dehalococcoides mccartyi CG1. CG1 preferentially removed halogens from the (−)-enantiomers of the three major environmentally relevant chiral PCBs (PCB174, PCB149, and PCB132), and the enantiomer compositions of the dechlorination products depended on their parent organohalides. The in vitro assays with crude cell extracts or concentrated whole cells and the in vivo experiments with living cells showed similar enantioselectivities, in contrast with the distinct enantiomeric enrichment factors (ε(ER)) of the substrate chiral PCBs. Additionally, these results suggest that concentrated whole cells might be an alternative to crude cell extracts in in vitro tests of reductive dehalogenation activities. The enantioselective dechlorination of other chiral PCBs that we resolved via gas chromatography further confirmed the preference of CG1 for the (−)-enantiomers. IMPORTANCE A variety of agrochemicals and pharmaceuticals are chiral. Due to the enantioselectivity in biological processes, enantiomers of chiral compounds may have different environmental occurrences, fates, and ecotoxicologies. Many chiral organohalides exist in anaerobic or anoxic soils and sediments, and organohalide-respiring bacteria play a major role in the environmental attenuation and global cycling of these chiral organohalides. Therefore, it is important to investigate the dehalogenation enantioselectivity of organohalide-respiring bacteria. This study reports the discovery of enantioselective dechlorination of chiral PCBs by Dehalococcoides mccartyi CG1, which provides insights into the dehalogenation enantioselectivity of Dehalococcoides and may shed light on future PCB bioremediation efforts to prevent enantioselective biological side effects.